2008
DOI: 10.1111/j.1751-8369.2008.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Ice-free conditions in Novaya Zemlya 35 000-30 000 cal years B.P., as indicated by radiocarbon ages and amino acid racemization evidence from marine molluscs

Abstract: Novaya Zemlya was covered by the eastern part of the Barents–Kara ice sheet during the glacial maximum of marine isotope stage 2 (MIS 2). We obtained 14C ages on 37 samples of mollusc shells from various sites on the islands. Most samples yielded ages in the range of 48–26 14C Ky. Such old samples are sensitive to contamination by young 14C, and therefore their reliability was assessed using replicate analyses and amino acid geochronology. The extent of aspartic acid racemization (Asp D/L) indicates that many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…The present study provides clear evidence of a significant northern component to the millennial timescale sea-level changes. Our observations also support emerging evidence of a much more dynamic Eurasian ice sheet than previously recognized, with retreat and advance closely linked to the Greenland interstadials and stadials 39,40 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study provides clear evidence of a significant northern component to the millennial timescale sea-level changes. Our observations also support emerging evidence of a much more dynamic Eurasian ice sheet than previously recognized, with retreat and advance closely linked to the Greenland interstadials and stadials 39,40 .…”
Section: Discussionsupporting
confidence: 88%
“…During MIS 4, c. 70-60 kyr BP, the Barents-Kara Sea (including Svalbard) and Scandinavia were covered by a huge confluent ice sheet [37][38][39][40][41] . The glaciation was followed by a rapid deglaciation, and from c. 55 to 25 kyr BP, the ice sheets on Svalbard and Scandinavia were apparently separated by an ice-free Barents Sea 37,40,41 . During the warmest period of MIS 3, 40-35 kyr BP, the Scandinavian ice sheet was most likely limited to the central part of Norway and Sweden 39,41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), but it does not necessarily preclude the presence of an additional ice dome southeast of Kong Karls Land in the Barents Sea. We have no evidence for such a dome, and the relatively low Holocene raised shorelines on Novaya Zemlya do not imply the presence of thick LGM ice farther east (Mangerud et al, 2008). There must have been an ice crest somewhere in the Barents Sea, probably located over the shallow Storbanken (~78°N).…”
Section: Discussionmentioning
confidence: 68%
“…Forman et al (2004) concluded that the pattern of postglacial emergence around the Barents Sea implied that the maximum ice load during the late Weichselian was located over the northern Barents Sea and eastern Svalbard. In addition, raised beaches of Holocene age in Novaya Zemlya are only 10-18 m above sea level, implying that LGM ice was thin here (Mangerud et al, 2008). On Franz Josef Land the maximum Holocene raised beaches are at 49 m (Forman et al, 1996), also suggesting that the greatest LGM ice loading was in the northwestern Barents Sea.…”
Section: Discussionmentioning
confidence: 97%